DEVELOPMENT OF CURRICULUM TO ENHANCE SPELLING AND COMBINED VOWEL SOUNDS BASED ON DAVIE’S INSTRUCTIONAL MODEL FOR GRADE 1 STUDENTS - Samniang, Rattikan (JOURNAL OF RATTANA PAÑÑĀ, 2020)
The purpose of this research are: 1) develop spelling and combined vowel sounds curriculum based on Davie’s instructional model for Grade 1 students 2) study the results of using the curriculum. The sample group was students in Primary class 1/7 totaled 41 students of Montfort College (Primary Section) selected by the simple random sampling method. The research instruments were: Development of curriculum to enhance reading words with spelling and combined vowel sounds based on Davie’s instructional model for Grade 1 students, a spelling and combined vowel sounds test. The instruments were the developed curriculum. Mean, Standard deviation, percentage were used for data analysis and t-test. The results found that: there was Development of curriculum to enhance reading words with spelling and combined vowel sounds based on Davie’s instructional model for Grade 1 students which composed of 6 learning units. The constructed curriculum had a suitable average, at a high level ( = 4.13, S.D = 0.64). The learning units and the lesson plans had a suitable average, at a high level ( = 4.21, S.D = 0.70). The results of the implementation were that average score for ability to spelling and combined vowel sounds test was significantly higher than that before implementing it (p<.05).